Effect of mixing and aeration on reactor temperature in aerobic thermophilic digestion process - Mishra, Manoj; Orth, H.M.; Samorn Muttamara; Shin, H.S.; The Netherlands Government (Bangkok : Asian Institute of Technology, 1986)
This study was conducted to detennine the effect of mixing and aeration on reactor temperature in Aerobic-Thermophilic Digestion Process. Experiments were conducted in a thenrally insulated reactor of an effective volume of 15 liters. Synthetic waste having 15,000 reg/l COD was used as feed and high purity oxygen gas, alongwith ordinary air, was used for aeration. Contrary to the claim of earlier researchers, results of this study found contribution of heat by exothermic metabolism of aerobic micro organisms to be of relatively less importance than that by mechanical mixing. Dominating role of heat input by mixing over biogenic heat was firmly established when reactor tenperature was maintained at 60.2oC without any biological activity inside the reactor. In accordance with the report;s of nost other researchers, aeration by high purity oxygen gas was observed to give a more stable process performance than the one due to aeration by ordinary air. COD remova 1 data obtained in this study indicated that maximum COD reduction was obtained at 510C - 520C reactor temperature and 9 - 11 ppm concentration of D.O. in mixed liquor.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Research Studies Project Report (M. Eng.) - Asian Institute of Technology, 1986
Keywords: Water-supply -- Nepal; Information storage and retrieval systems -- Water-supply